2013
DOI: 10.1186/1742-4933-10-33
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity for CMV and IL-6 levels are associated with grip strength and muscle size in the elderly

Abstract: BackgroundSarcopenia is an important cause of morbidity and mortality in older adults, with immunosenescence and inflammation being possible underlying mechanisms. We investigated the relationship between latent cytomegalovirus (CMV) infection, Interleukin 6 (IL-6) levels, muscle size and strength in a group of healthy older community-dwelling people.MethodsParticipants were healthy volunteers from the Lothian Birth Cohort 1936 study. Participants had IL-6 level and CMV antibody titre measured at age 70 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 43 publications
2
24
1
Order By: Relevance
“…Despite this, no published epidemiological data exists investigating the relationship between CMV and B‐CLL prognosis. This work, reports the prevalence of HCMV within the two cohorts was approximately 60%–70%, which is comparable with studies of viral seroprevalence in healthy people at a similar median age of 64 years 23. As such we find no evidence that CMV infection is associated with the development of B‐CLL.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Despite this, no published epidemiological data exists investigating the relationship between CMV and B‐CLL prognosis. This work, reports the prevalence of HCMV within the two cohorts was approximately 60%–70%, which is comparable with studies of viral seroprevalence in healthy people at a similar median age of 64 years 23. As such we find no evidence that CMV infection is associated with the development of B‐CLL.…”
Section: Discussionsupporting
confidence: 87%
“…This may be due partly to the younger age of the patients with B‐CLL compared with studies of healthy elderly people, which have focused predominantly on those between 70 and 100 years of age 11, 28, 29. In addition, the detrimental impact of chronic HCMV on the health of older people has been linked with elevated levels of inflammatory markers, including IL‐6 23, 30, 31, which are often already increased in patients with B‐CLL and may therefore confound any impact of HCMV on further health outcomes 32, 33. It may also suggest that any negative effect of HCMV infection in the elderly is outweighed by a diagnosis of B‐CLL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study where CMV serostatus was not associated with frailty (Collerton et al 2012). Another recent study by Kilgour et al found a significant impact of CMV serostatus on HGS in women, but not men (both 72 years old), a significant negative correlation of CMV antibody titers with HGS (right hand in women and left hand in men) and a negative correlation of IL-6 titers with HGS in men, but not women (Kilgour et al 2013). In the BASE-II cohort no correlations of HGS with IL-6 levels were observed, but again elderly men seemed to be differently affected, as IL-6 concentrations were significantly higher compared to women.…”
Section: Discussionmentioning
confidence: 93%
“…Potential clinical relevance of such results is illustrated for example in reports of associations of IL-6 levels with survival of the very elderly (Wikby et al 2006). IL-6 levels correlated in another study negatively with HGS, wherein CMV serostatus and antibody titers did not correlate with IL-6 levels (Kilgour et al 2013). In addition, inflammation in the elderly-determined by IL-1RA, IL-6, CRP and TNF levels-was demonstrated to be associated with adiposity and lower survival (Lisko et al 2012).…”
Section: Discussionmentioning
confidence: 95%